LECTINS AND THEIR APPLICATION IN FORENSIC MEDICAL PRACTICE - Mukharrama A. Khasanova; Nizom J. Ermatov (Central Asian Journal of Medicine, 2022)
The problem of obtaining economically cheap drugs for determining the group (in liquid form and in traces) is relevant. Diagnostic lectinology in relation to the determination of the blood group of the AB0 system is currently widely used in many countries of the world. The commercial cost of lectins is tens and even hundreds of times lower than the cost of rabbit absorption serum. The study of lectins in the seeds of some plants growing on the territory of Uzbekistan has shown the possibility of using them in the determination of antigens of the AB0 system.